2014
DOI: 10.14402/jkamprs.2014.36.2.50
|View full text |Cite
|
Sign up to set email alerts
|

Bone Induction by Demineralized Dentin Matrix in Nude Mouse Muscles

Abstract: Purpose:This study examined the osteoinductive activity of demineralized human dentin matrix for nude mice.Methods:Twenty healthy nude mice weighing about 15 to 20 g were used for study. Demineralized human dentin matrix was prepared and implanted into the dorsal portion of nude mice (subcutaneous), which were sacrificed at two, four, and eight weeks after demineralized dentin matrix grafting and evaluated histologically by H&E and Masson trichrome staining. The specimens were also evaluated histomorphometrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…34 Interestingly, our data suggested that demineralized deciduous teeth contain much more BMP-2 with respect to native and demineralized dentin, 15 which are currently considered to be among the most suitable substitutes used for bone repair and regeneration. 25,[35][36][37] Such findings all strengthen the idea that BTs are very attractive bioactive materials for use in autologous bonegrafting procedures.…”
Section: Demineralization Effect On Type I Col-i and Bmp-2 Protein Cosupporting
confidence: 61%
“…34 Interestingly, our data suggested that demineralized deciduous teeth contain much more BMP-2 with respect to native and demineralized dentin, 15 which are currently considered to be among the most suitable substitutes used for bone repair and regeneration. 25,[35][36][37] Such findings all strengthen the idea that BTs are very attractive bioactive materials for use in autologous bonegrafting procedures.…”
Section: Demineralization Effect On Type I Col-i and Bmp-2 Protein Cosupporting
confidence: 61%
“…1). Dentin demineralization with 0.6 N HCl results in the elimination of the major part of the mineral phase and immunogenic components, while retaining a very low fraction of minerals (5-10 wt.%), the majority of type I collagen, and NCPs, providing an osteoconductive and osteoinductive scaffold containing several growth factors 35) (Fig. 1).…”
Section: Characterization Of Demineralized Dentin Matrix (Ddm) Micropmentioning
confidence: 99%
“…In fact, D, in the form of native D (8, 9), and D derivatives, such as demineralized (10-11-12-13) and deproteinized D (14), have been used as graft materials in bone repair processes. Some experimental evidence from a critical literature survey highlighted the role of demineralized D matrix in promoting osteodifferentiation in vitro (13) and, even more interestingly, in increasing osteoinduction in vivo (15, 16). Taken together, these works point to the use of demineralized D matrices for the treatment of bone defects.…”
Section: Introductionmentioning
confidence: 99%